If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x/9-7=33
We move all terms to the left:
5x/9-7-(33)=0
We add all the numbers together, and all the variables
5x/9-40=0
We multiply all the terms by the denominator
5x-40*9=0
We add all the numbers together, and all the variables
5x-360=0
We move all terms containing x to the left, all other terms to the right
5x=360
x=360/5
x=72
| -(6/w)=-8 | | F(x)=(2x+3)(x-2x) | | -6(-3u+6)-5u=7(u-4)-5 | | 37=-2(22-m)+3(m-3) | | -2w-25=9(w+7) | | 3x=(12)(18) | | -7(v+2)+2v+7=6v+9 | | 43x-17-3x=19+40x-36 | | 3+15y-1=9y+57-5y | | 6x^2–3=–18x | | 5x^2=3x+23 | | 0=-4z+40 | | 4x+5/8x+5x=10 | | 2b^2=100 | | 2y2−2y−5=0 | | 4(3^-2x-4)=36 | | 5x2+9x=13x−3 | | 3y2=54 | | 16=-8v+4(v+6) | | -7=7y+7(y-3) | | 33=-6x+3(x+5) | | 15x^2+7x-20=-20 | | x2−14x+17=0 | | 2x2+4=10 | | |3x+4|=|x-13| | | -2a+40+9a=3a-6a | | 2x2=10 | | 8-2x-6-13x=5 | | 12x-97=119 | | X(x-4)-2=x2-4(x+3) | | x2−4x−3=0 | | 4(x+1)=6-x |